2020
DOI: 10.1109/access.2020.3032462
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent Evaluation System of Government Emergency Management Based on BP Neural Network

Abstract: With the deepening of the global economic community, various emergencies emerge in endlessly, and the risks gradually increase. People's lives and property are threatened, which also causes a great burden on the social economy. Hitherto unknown novel coronavirus events occurred in China after the outbreak of the new coronavirus in 2019. The emergency management system is not perfect, so we start to study and improve the deficiencies of the emergency management system, but it is still difficult to effectively p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Neurons of a layer only receive neural signals from the previous layer and those at the same layer do not have any connections with each other. The number of hidden layers, the number of neurons in each layer, and the network learning rate can be adjusted or set based on specific needs (Jia and Wu 2020 ; Zhu et al 2021 ), as shown in Fig. 1 .…”
Section: Methodology and Datamentioning
confidence: 99%
“…Neurons of a layer only receive neural signals from the previous layer and those at the same layer do not have any connections with each other. The number of hidden layers, the number of neurons in each layer, and the network learning rate can be adjusted or set based on specific needs (Jia and Wu 2020 ; Zhu et al 2021 ), as shown in Fig. 1 .…”
Section: Methodology and Datamentioning
confidence: 99%
“…According to the abovementioned FPN assessment model, the content of government emergency management decisions should focus on one or more aspects [ 61 , 62 ], such as risk perception, pre-security, monitoring and warning, emergency response, and emergency review. Therefore, to achieve the goal of the best governance effect, the content of public panic emergency management concerns should have primary and secondary importance and be selective.…”
Section: Construction Of the Modelmentioning
confidence: 99%
“…Adini [ 9 ] designed an assessment system to measure the organization's emergency preparedness level, which contains four dimensions: SOPs, training and drills, staff literacy, and infrastructure and equipment. DIAN JIA [ 10 ] established an intelligent evaluation system for government emergency management based on an IoT environment. Through practical application, they proved that the system has strong execution capability, outstanding big data computing capability, and can objectively evaluate and analyze government emergency management work.…”
Section: Literature Reviewmentioning
confidence: 99%